Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3892/mco.2019.1909
|View full text |Cite
|
Sign up to set email alerts
|

Treatments and outcomes of older patients with esophageal cancer: Comparison with younger patients

Abstract: The number of older patients with esophageal cancer (EC) is increasing due to the population aging and increasing life expectancy. However, no optimal treatment strategy for older patients with EC has been established to date. The aim of the present study was to review and compare the treatment modalities and outcomes of 990 younger and older patients diagnosed with EC in our institution. The patients were divided into younger (≤74 years) and older (≥75 years) groups. The majority of the patients in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…However, in a previous propensity score-matched study, patients with T1N0 EC who underwent local therapy had similar overall survival but improved EC-specific survival compared with those who underwent oesophagectomy, which meant that local therapy may reduce procedure-related death (9). In addition, Matsumoto and colleagues performed a single centre retrospective study and found that the prognosis following oesophagectomy was not better than that of chemoradiotherapy in elderly patients with stage I EC (18). Accordingly, the assessment of surgical tolerance among patients with pT1a stage EC who have potentially lifelimiting medical conditions or comorbidities was critical, and palliative chemoradiotherapy or local therapy may be considered as treatment options for this population (4,9,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous propensity score-matched study, patients with T1N0 EC who underwent local therapy had similar overall survival but improved EC-specific survival compared with those who underwent oesophagectomy, which meant that local therapy may reduce procedure-related death (9). In addition, Matsumoto and colleagues performed a single centre retrospective study and found that the prognosis following oesophagectomy was not better than that of chemoradiotherapy in elderly patients with stage I EC (18). Accordingly, the assessment of surgical tolerance among patients with pT1a stage EC who have potentially lifelimiting medical conditions or comorbidities was critical, and palliative chemoradiotherapy or local therapy may be considered as treatment options for this population (4,9,18).…”
Section: Discussionmentioning
confidence: 99%
“…Age per se should not be the sole factor for or against trimodal therapy [ 43 46 ]. Scoring systems like P-POSSUM or O-POSSUM and predictive models as published by Steyerberg et al and, more recently, by the International Esodata Study group should be considered by stratifying our patients for more or less aggressive therapy regimens [ 47 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of EC is increasingly accepted for elderly people defined as aged over 70 years. Not differing outcome and long-term results in the selected elderly from those reported for younger patients offer the possibility of risk/opportunity stratification and assessment [47][48][49][50]. Here, based on a comparison of the CROSS trial with historical controls (e.g., RTOG 8501 and Intergroup [INT] 0123) and retrospective studies, radiosensitizing with Carb/TAX seems more tolerable than cisplatin/5-fluorouracil [51][52][53].…”
Section: Discussionmentioning
confidence: 99%